Stressor‐response relationships and the prospective management of aquatic ecosystems - Scott T. Larned; Marc Schallenberg (New Zealand Journal of Marine and Freshwater Research, 2019)
Scientists and environmental managers use stressor‐response (S‐R) relationships to characterise and predict ecological and socioeconomic responses to anthropogenic stressors in lakes and other aquatic ecosystems. S‐R relationships with thresholds (stressor levels beyond which small increases cause large responses) are reported with increasing frequency. Threshold responses pose risks of unanticipated degradation, but also provide a stimulus for shifting environmental management strategies from retrospective (focused on post‐hoc responses to degradation) to prospective (focused on preventing degradation). We set out a framework for interpreting S‐R relationships in terms of functional forms, trajectories, thresholds and slopes. These characteristics convey information about resistance to degradation and recovery, risks of threshold exceedance, and alternate stable states. We then set out steps for implementing threshold‐based management strategies, which are based on forecasting S‐R relationships and carrying out preventative actions within an adaptive framework. Prospective, threshold‐based management is a challenging yet promising alternative to the prevailing retrospective strategies.